If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(-2/7)*x = 6 // - 6
(-2/7)*x-6 = 0
-2/7*x-6 = 0 // + 6
-2/7*x = 6 // : -2/7
x = 6/(-2/7)
x = -21
x = -21
| 2x/3-4=5/4 | | 6m+6m^2+4= | | -5#+33=83 | | (3a-3)^2/(5a-5) | | y=-4x-(-7) | | (3a-3)^2/(5a-5)^2 | | 4n^2-10=5n | | (-3x^4+7x^2+1)-(x^4+6x^2-9)= | | 344+96x=1400 | | 344+96x= | | 92+2x= | | 13-1/3u=2 | | 10x+8=10x-12 | | 2x+92= | | 3x+11=6x | | 180-139.2= | | -10(4x+8)=80 | | 4b^2=17+b | | (18x-3)/3 | | 18x-3/3 | | 6x+10=4x+40 | | 38+38+38= | | n-5/2=-5 | | W-17/w^2-2w-3 | | (1/3)w-5=(-7/4)w-(1/3) | | -0.1(40)+0.4x=0.2(40+x) | | 68+(2x+18)=90 | | -400=-50x+50 | | (2x^2+9x-5)+(2x^2+3x+11)-(4x^2-17)= | | 3y-5/5=6y-5/11 | | 74+(4x+12)=90 | | -12x+8=-52 |